2017
DOI: 10.1016/j.vaccine.2016.12.021
|View full text |Cite
|
Sign up to set email alerts
|

Passive antibodies derived from intramuscularly immunized toxoid fusion 3xSTa N12S -dmLT protect against STa+ enterotoxigenic Escherichia coli (ETEC) diarrhea in a pig model

Abstract: Enterotoxigenic Escherichia coli (ETEC) strains are among the most common causes of children’s diarrhea and travelers’ diarrhea. Developing effective vaccines against ETEC associated diarrhea becomes a top priority. ETEC heat-labile toxin (LT) and heat-stable toxin (STa) toxoid fusion 3xSTaN12S-dmLT was demonstrated recently to induce neutralizing antitoxin antibodies in intraperitoneally or subcutaneously immunized mice. However, whether antibodies derived from this toxoid fusion are protective against ETEC d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
39
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 27 publications
(40 citation statements)
references
References 28 publications
(36 reference statements)
1
39
0
Order By: Relevance
“…Based on PCR analysis, we observed fewer Lactobacillus and more Enterobacteriaceae in TGEV-infected pigs. Among Enterobacteriaceae family, Escherichia coli is the most common cause of diarrhea in pigs and piglets [22][23][24]. Research has shown that animals with signs of intestinal disease have far greater numbers of Enterobacteriaceae than do healthy individuals, and that the Enterobacteriaceae are linked to intestinal disorders [25,26].…”
Section: Discussionmentioning
confidence: 99%
“…Based on PCR analysis, we observed fewer Lactobacillus and more Enterobacteriaceae in TGEV-infected pigs. Among Enterobacteriaceae family, Escherichia coli is the most common cause of diarrhea in pigs and piglets [22][23][24]. Research has shown that animals with signs of intestinal disease have far greater numbers of Enterobacteriaceae than do healthy individuals, and that the Enterobacteriaceae are linked to intestinal disorders [25,26].…”
Section: Discussionmentioning
confidence: 99%
“…57,81,[89][90][91][92] Three copies of an STh-N12S mutant genetically fused with dmLT, 3xSTh N12S -dmLT, was identified as a promising vaccine candidate that may engender neutralizing antibodies against both ST and LT. 84,85,92 Notably, piglets born from 3xSTh N12S -dmLT immunized pregnant gilts seemed to be passively protected from ETEC diarrhea during challenge. 85 The 3xSTh N12S -dmLT construct was further genetically fused to seven putative immunodominant colonization factor epitopes from prevalent ETEC strains (CFA/I/II/IV). 57 Interestingly, the expressed single polypeptide immunogen elicited anti-adhesin antibodies against all the seven CFA in addition to anti-ST and anti-LT antibodies in mice.…”
Section: St-carrier Genetic Fusionmentioning
confidence: 94%
“…57,58 The non-toxic double mutant LT (dmLT; LT R192G/L211A ) has also been used as a carrier, offering the additional benefit of engendering neutralizing anti-LT antibodies. [83][84][85] Additionally, an LT-STh P13F fusion was incorporated into a live attenuated oral E. coli vaccine (ZCR533) that constitutively express the antigen on its surface or as a secretion. 86…”
Section: Making St Immunogenic By Coupling It To a Protein Carriermentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, ETEC adhesin antigen CFA/I/II/IV MEFA (multiepitope fusion antigen), carrying epitopes of the seven most prevalent adhesins (CFA/I, CFA/II [CS1, CS2, and CS3], and CFA/IV [CS4, CS5, and CS6]), was demonstrated to induce antibodies against adherence of ETEC and E. coli bacteria expressing these seven CFA adhesins in vitro (18). Recent studies also showed that genetic fusions of an STa toxoid and a monomeric LT (mnLT; one LT A domain and one LT B domain as a single peptide) induced antitoxin antibodies to neutralize both toxins (19)(20)(21)(22)(23)(24).…”
mentioning
confidence: 99%